2015
DOI: 10.1016/j.lwt.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of various chemical parameters of olive oils with Fourier transform infrared spectroscopy

Abstract: a b s t r a c tVibrational spectroscopic techniques offer advantages such as rapid and accurate measurements with minimum sample preparation and waste generation. In this study, it was aimed at determining some important quality parameters (oxidative stability, colour pigments, fatty acid profile and phenolic composition) of olive oils by Fourier transform infrared spectroscopy as one of the vibrational spectroscopic methods. Partial least square calibration models were constructed in order to reveal any corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 28 publications
3
45
0
4
Order By: Relevance
“…It was also observed that high total phenol content did not necessarily cause stability, but rather carotenoids and individual phenolic substances such as hydroxytyrosol and tyrosol did. The significant effects of hydroxytyrosol and total hydroxytyrosol and tyrosol concentrations on the oxidative stability were reported by other researchers (Allalout et al, 2009;Uncu & Ozen, 2015).…”
Section: Multivariate Analysissupporting
confidence: 62%
“…It was also observed that high total phenol content did not necessarily cause stability, but rather carotenoids and individual phenolic substances such as hydroxytyrosol and tyrosol did. The significant effects of hydroxytyrosol and total hydroxytyrosol and tyrosol concentrations on the oxidative stability were reported by other researchers (Allalout et al, 2009;Uncu & Ozen, 2015).…”
Section: Multivariate Analysissupporting
confidence: 62%
“…As a last parameter, variable importance for the projection (VIP) values for geographical origin and harvesting year, generated with SIMCA software, were used to determine the most influential variables of pigment and wavelength and/or wavenumber in chromatographic and spectral analysis respectively. Variables having VIP values greater or close to 1 were considered as important variables in classification …”
Section: Methodsmentioning
confidence: 99%
“…phenolics, tocopherols, and pigments) that are associated with its health benefits . These chemical characteristics of olive oils are well preserved during its production, which is based on mechanical extraction without the use of any chemical solvent . Owing to the high demand for this product, various types of inauthentic products have been supplied to the market to obtain unfair gain .…”
Section: Introductionmentioning
confidence: 99%
“…Mid-infrared spectroscopy was tested for quantitative determinations of saturated and unsaturated fatty acids in olive oil samples [48], fatty acids, and triacylglycerols in virgin olive oils [49], and oleic acid, linoleic acid, saturated fatty acids, mono-unsaturated fatty acids and poly-unsaturated fatty acids in virgin olive oils [50]. Apart from the fatty acid composition, the information contained in the infrared spectrum was used to estimate other qualitative parameters such as water content, total phenol amount, and antioxidant activity in virgin olive oils [51], as well as the phenolic and chlorophyll contents in olive oils [52] and the fatty acid alkyl ester amounts in extra virgin olive oils [53]. Different stages of the oxidation process of extra virgin and olive oils have been shown to involve changes in FT-IR spectrum frequency values of different bands and in ratios between absorbances of some bands [54]; these changes appear to be related to variations in peroxide and anisidine values levels occurring during the oxidation course [55].…”
Section: Nir Mir and Raman Spectroscopymentioning
confidence: 99%